2010
DOI: 10.4085/1062-6050-45.3.259
|View full text |Cite
|
Sign up to set email alerts
|

A Description of Shock Attenuation for Children Running

Abstract: Vegas. Dr Mangus is now at Texas A&M University-Commerce.Context: A growing number of children are participating in organized sport activities, resulting in a concomitant increase in lower extremity injuries. Little is known about the impact generated when children are running or how this impact is attenuated in child runners.Objective: To describe shock attenuation characteristics for children running at different speeds on a treadmill and at a single speed over ground.Design: Prospective cohort study. Settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…For each stride, the peak left leg and head acceleration values were obtained and used to calculate shock attenuation using the following formula: [1 -(head peak / leg peak)] x 100 (26). Thus, a larger value was indicative of greater impact attenuation (25). For each foot strike pattem, the average shock attenuation of the 15 strides per subject was calculated and evaluated statistically (Fig.…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…For each stride, the peak left leg and head acceleration values were obtained and used to calculate shock attenuation using the following formula: [1 -(head peak / leg peak)] x 100 (26). Thus, a larger value was indicative of greater impact attenuation (25). For each foot strike pattem, the average shock attenuation of the 15 strides per subject was calculated and evaluated statistically (Fig.…”
Section: Samplementioning
confidence: 99%
“…Shock attenuation, the dissipation ofthe impact that occurs during initial contact of foot with the ground, is dependent on passive structures of the body and active movement. It can be influenced by running speed, stride length, and state of fatigue (25). If shock attenuation could change by running a different way, then perhaps injiuy and pain in the low back could change as well.…”
mentioning
confidence: 99%
“…Shock attenuation represents the mechanical process by which transient energy diminishes as it propagates through the musculoskeletal system (Valiant, 1990). Shock attenuation is achieved via muscle contraction, lower body alignment and passive musculoskeletal tissue deformation (Mercer et al, 2010). A further discrepancy is that Dufek et al (2009) quantified transient attenuation from the tibia to the head as opposed to the sacrum.…”
Section: Discussionmentioning
confidence: 99%
“…Shock attenuation is therefore an essential parameter when quantifying impact transients during running, as it serves a quantifiable indicator of the extent to which the impact shock wave is reduced (Shorten, Winslow, 1992). The mechanical process by which shock is attenuated is through the absorption of energy via muscle contraction, lower extremity alignment and deformation of passive musculoskeletal structures (Mercer et al, 2010). It has been shown that can be mediated by a number of different biomechanical/ anthropometrical parameters (Mercer et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation